1994
DOI: 10.2135/cropsci1994.0011183x003400050003x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Selection for Tolerance to Bean Yellow Mosaic Virus in Arrowleaf Clover

Abstract: Arrowleaf clover (Trifolium vesiculosum Savi) is an important forage crop in the southeastern USA, but production and persistence of arrowleaf can be limited by virus diseases. We conducted five cycles of recurrent phenotypic selection from 1986 through 1991 for tolerance to bean yellow mosaic virus (BYMV) isolate KY 204‐1 in arrowleaf clover. Six‐week‐old seedlings were mechanically inoculated with BYMV and evaluated at 100 d of age. From 300 to 1100 plants were screened per cycle, and the most tolerant 1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Pederson and McLaughlin (1994) found that the reaction of white clover clones to AMV in the field was not well related to performance of progeny under mechanical inoculation in the greenhouse. However, Pemberton et al (1994) showed improved field performance in the presence of bean yellow mosaic virus in populations selected in the greenhouse for tolerance to this same virus. The present study has shown that resistance to AMV in red clover is under polygenic control.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Pederson and McLaughlin (1994) found that the reaction of white clover clones to AMV in the field was not well related to performance of progeny under mechanical inoculation in the greenhouse. However, Pemberton et al (1994) showed improved field performance in the presence of bean yellow mosaic virus in populations selected in the greenhouse for tolerance to this same virus. The present study has shown that resistance to AMV in red clover is under polygenic control.…”
Section: Resultsmentioning
confidence: 97%
“…The fact that only two (R × R) × ( R × R) crosses produced sufficient progeny (Table 1) can be explained by cross-incompatibilities caused by the small base population. Pemberton et al (1994) carried out five cycles of recurrent phenotypic selection for tolerance to bean yellow mosaic virus in arrowleaf clover (Trifolium vesiculosum Savi) and produced a highly tolerant population.…”
Section: Resultsmentioning
confidence: 99%
“…In 1979, a forage breeding program was initiated at the Texas Agriculture Experiment Station (TAES), Overton, to develop improved, disease‐resistant cultivars. ‘Apache’ arrowleaf clover, released by TAES in 2004 (Smith et al, 2004), was developed through multiple cycles of recurrent selection for tolerance to Bean yellow mosaic virus (Pemberton et al, 1989, 1991, 1994) and soil‐borne fungal pathogens such as Pythium ultimum Trow (Pemberton et al, 1998). The release of Apache has restored the utility of arrowleaf clover for livestock production systems in the southern United States.…”
mentioning
confidence: 99%
“…mosaic virus (Pemberton et al, 1989(Pemberton et al, , 1991(Pemberton et al, , 1994 and soil-borne fungal pathogens such as Pythium ultimum Trow (Pemberton et al, 1998). The release of Apache has restored the utility of arrowleaf clover for livestock production systems in the southern United States.…”
mentioning
confidence: 99%
“…The dominant allele, L , imparting the systemic wilting response to BYMV, is present in 15 to 23% of the Yuchi arrowleaf clover population. One cycle of selection, with mechanical inoculation with BYMV‐KY204‐1 eliminated the susceptible ( LL and Ll ) genotypes (Pemberton et al, 1994).…”
mentioning
confidence: 99%